The Influence of CSR on the Reputation of ABC Bank - Pamungkas, Nugroho; Aditama, M Danial Prasetiyo; Prima, Adnan Dianda; Harto, Puji; Raharja, Surya (LifeSciFi, 2024)
Bank ABC is one of Indonesia's largest banks and a state-owned enterprise. A bank's reputation is critical in attracting customers, maintaining stakeholder trust, and influencing the company's position in the market. What is believed to affect the bank's reputation is a social and environmental concern known as Corporate Social Responsibility (CSR). Therefore, this study aims to examine the influence of three CSR programs of Bank ABC on the bank's reputation. The three CSR programs have been measured for their usefulness to the community using the Social Return on Investment (SROI) method. Data were collected through a survey with respondents from the community of banking service users and CSR beneficiaries of Bank ABC. The purposive sampling method became the sample method of this research. Hypothesis testing was conducted using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method. Program 2 (Bank Sampah Saguling) and Program 3 (Sortir Lemon) produced significant results based on the SEM-PLS results. At the same time, Program 1 (Ini SekolahKu) produced insignificant results. Therefore, backward elimination was carried out with a significance level of 5%. Using backward elimination, it was obtained that Program 2 (Saguling Garbage Bank) and Program 3 (Sort Lemon) influenced ABC Bank's Reputation with an R^2 value of 78.3%.